RESPON STRUKTUR AKIBAT PENEMPATAN DILATASI PADA BANGUNAN DENGAN KETIDAKBERATURAN HORIZONTAL - Lilis Tiyani; Amalia; Rezki Nur Fadlli; Jonathan Saputra (Universitas Widyatama, 2022)
The placement of dilation in the building structure with horizontal irregularity causes a different response to the structure during an earthquake, because the structure is divided into several individual structures that stand alone so that they are different from the original structure. The proper placement of the dilation in a building will reduce the risk of collapse of the building during an earthquake as well potentially making structures simpler and more efficient. This study uses the design analysis method to compare the earthquake shear force, structural response, and internal forces in the structure due to the placement of the X-direction and Y-direction Dilatation. greater than the X direction dilatation, which is 42% in the X direction and 38% in the Y direction. The deviation that occurs in the Y direction dilation is greater than the X direction dilatation. X, but the internal force due to the Y direction of dilation on the beam is greater than the X direction dilation placement. So that the use of the Y direction dilation is slightly better than the use of the X direction dilatation in several things, such as the earthquake force and the inner force on the smaller column.